2021
DOI: 10.1007/s00402-021-03794-3
|View full text |Cite
|
Sign up to set email alerts
|

The subjective knee value is a valid single-item survey to assess knee function in common knee disorders

Abstract: Introduction The patient’s perspective plays a key role in judging the effect of knee disorders on physical function. We have introduced the Subjective Knee Value (SKV) to simplify the evaluation of individual’s knee function by providing one simple question. The purpose of this prospective study was to validate the SKV with accepted multiple-item knee surveys across patients with orthopaedic knee disorders. Materials and methods Between January through Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Faster to answer and more intuitive single-item scores can also lead to higher response rates and more fully completed questionnaires, as Plachel et al showed with a similar score for the knee. Here, significantly higher rates of complete responses were shown for the single-item score compared to more complex multi-item scores [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faster to answer and more intuitive single-item scores can also lead to higher response rates and more fully completed questionnaires, as Plachel et al showed with a similar score for the knee. Here, significantly higher rates of complete responses were shown for the single-item score compared to more complex multi-item scores [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, subjective single item scores have been developed in musculoskeletal research for the (time-) efficient assessment of subjectively perceived joint-specific function [ 12 , 13 , 20 , 26 ]. These valid scores show good correlation with multi-item scores and can be applied to a variety of pathologies and are regularly used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SANE is a simple method of evaluating patients' sense of functional improvement after meniscal repair surgery and rating for current illness score about their pre-injury baseline on a range of 0 to 100. SANE scores are most commonly used by orthopedic sports specialist surgeons, and usually for the shoulder and the knee [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Согласно определению Всемирной организации здравоохранения, качество жизни является личным восприятием своего собственного жизненного плана в контексте систем культуры и ценностей, в которых человек живет в соответствии со своими целями, ожиданиями, стандартами и интересами [7]. Концепция КЖ динамично развивается, расширяются сферы ее применения в различных областях медицины и здравоохранения 1 [8][9][10][11][12], для всесторонней оценки эффективности проводимого лечения и реабилитации [13][14][15].…”
Section: Introductionunclassified